2009
DOI: 10.4321/s0004-06142009000300009
|View full text |Cite
|
Sign up to set email alerts
|

Indicación actual de la cirugía abierta en el tratamiento de la litiasis renal: Ureterocalicostomía como tratamiento definitivo de litiasis en mujer con patología recidivante

Abstract: Ureterocalicostomy is indicated in cases of ureteropelvic junction obstruction associated with intrarenal pelvis caused by alterations of fusion, rotation or location of kidney. It is also indicated in cases of severe peripyelic fibrosis secondary to previous pyeloplasty failure or renal surgery. In our case, in addition to the infectious component of lithiasis, an anatomical alteration, probably secondary to previous surgery, caused the chronification of lithiasis. Facing such suspicion a surgical management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…One patient experienced rapid stenosis but was successfully treated endoscopically, while another patient had a poor outcome and ultimately required nephrectomy. As reported by Mijan et al [ 28 ], UC has been found to be a viable treatment option for intrapelvic UPJO resulting from changes in the fusion, rotation, or location of the kidney. It can also be used for severe peripelvic fibrosis cases where previous pyeloplasty or renal surgery has been unsuccessful.…”
Section: Open Ureterocalicostomymentioning
confidence: 87%
“…One patient experienced rapid stenosis but was successfully treated endoscopically, while another patient had a poor outcome and ultimately required nephrectomy. As reported by Mijan et al [ 28 ], UC has been found to be a viable treatment option for intrapelvic UPJO resulting from changes in the fusion, rotation, or location of the kidney. It can also be used for severe peripelvic fibrosis cases where previous pyeloplasty or renal surgery has been unsuccessful.…”
Section: Open Ureterocalicostomymentioning
confidence: 87%